Profiles of Deceased Patients with Coronavirus Disease 2019 (COVID-19) and Multidrug-Resistant Bacterial Coinfections at an Indonesian Tertiary Hospital - Firmansyah, Joedhistira Bayu; Rusli , Musofa; Juniastuti; Septyawati, Ratna (Universitas Airlangga, 2025)
Introduction: Antibiotic use in coronavirus disease 2019 (COVID-19) patients reached 70% during the pandemic, potentially inducing the invasion of multidrug-resistant organisms (MDROs). This study analyzed patients who died from COVID-19 with MDRO coinfections at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: We conducted a retrospective descriptive study of 120 deceased COVID-19 inpatients from January to December 2021. The inclusion criteria required: (1) positive MDRO cultures from ≥2 specimens, and (2) resistance to ≥1 agent across ≥3 antimicrobial categories. Patients with incomplete records or no antibiotic therapy were excluded. The data were presented using descriptive statistics to characterize patient demographics, microbiological profiles, and antimicrobial resistance patterns. Results: The patients were predominantly male (60%), aged 41–80 years (78.33%), and hospitalized for 8–30 days (53.44%). The microbiological examinations revealed blood cultures as the main specimen source (43.10%), followed by sputum (27.59%), urine (19.40%), pus (7.33%), and cerebrospinal fluid (2.59%). The prevalent isolates varied by specimen type: coagulase-negative staphylococci (51%) in blood, Pseudomonas spp. in pus (17.65%), Klebsiella spp. in sputum (26.69%), and Escherichia coli in urine (37.78%). The cerebrospinal fluid cultures showed an equal distribution of Gram-negative bacilli, Gram-positive bacilli, and Gram-positive cocci (33.33% each). Conclusion: This study characterizes the profiles of fatal COVID-19 cases with MDRO coinfections, demonstrating a predominance of older male patients with prolonged hospitalization. The identified resistance patterns and pathogen distribution, notably coagulase-negative staphylococci in blood, highlight the importance of improved infection surveillance and antibiotic stewardship to minimize the risk of coinfection in the future. Highlights: 1. While existing studies have examined multidrug-resistant organism (MDRO) coinfections in COVID-19 globally, this work offers a valuable standalone characterization of a high-risk subgroup in Indonesia, where resistance patterns arising from antimicrobial use during the pandemic created unique clinical challenges. 2. This study provides comprehensive data on the mortality of COVID-19 patients with MDRO coinfections at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, enhancing medical personnel's awareness of MDRO bacterial transmission and informing improvements in antibiotic stewardship programs within hospitals.